Gut bacteria of the silkworm Bombyx mori facilitate host resistance against the toxic effects of organophosphate insecticides. (October 2020) - Chen, Bosheng; Zhang, Nan; Xie, Sen; Zhang, Xiancui; He, Jintao; Muhammad, Abrar; Sun, Chao; Lu, Xingmeng; Shao, Yongqi
Abstract: Organophosphate insecticides that are heavily used in agriculture for pest control have caused growing environmental problems and public health concerns worldwide. Ironically, insecticide resistance develops quickly in major lepidopteran pests, partially via their microbial symbionts. To investigate the possible mechanisms by which the microbiota confers insecticide resistance to Lepidoptera, the model organism silkworm Bombyx mori (Lepidoptera: Bombycidae) was fed different antibiotics to induce gut dysbiosis (microbiota imbalance). Larvae treated with polymyxin showed a significantly lower survival rate when exposed to chlorpyrifos. Through high-throughput sequencing, we found that the abundances of Stenotrophomonas and Enterococcus spp. changed substantially after treatment. To assess the roles played by these two groups of bacteria in chlorpyrifos resistance, a germ-free (GF) silkworm rearing protocol was established to avoid the influence of natural microbiota and antibiotics. Monoassociation of GF silkworms with Stenotrophomonas enhanced host resistance to chlorpyrifos, but not in Enterococcus -fed larvae, consistent with larval detoxification activity. GC-μECD detection of chlorpyrifos residues in feces indicated that neither Stenotrophomonas nor Enterococcus degraded chlorpyrifos directly in the gut. However, gut metabolomics analysis revealed a highly species-specific pattern, with higher levels of essential amino acid produced in the gut of silkworm larvae monoassociated with Stenotrophomonas . This critical nutrient provisioning significantly increased host fitness and thereby allowed larvae to circumvent the deleterious effects of these toxic chemicals more efficiently. Altogether, our study not only suggests a new mechanism for insecticide resistance in notorious lepidopteran pests but also provides a useful template for investigating the interplay between host and gut bacteria in complex environmental systems.